Potential thiosemicarbazone‐based enzyme inhibitors: Assessment of antiproliferative activity, metabolic enzyme inhibition properties, and molecular docking calculations. Issue 5 (24th February 2022) - Yakan, Hasan; Koçyiğit, Ümit M.; Muğlu, Halit; Ergul, Mustafa; Erkan, Sultan; Güzel, Emre; Taslimi, Parham; Gülçin, İlhami
Abstract: A new series of thiosemicarbazone derivatives (1 –11 ) were prepared from various aldehydes and isocyanates with high yields and practical methods. The structures of these compounds were elucidated by Fourier transform infrared, 1 H‐nuclear magnetic resonance (NMR), 13 C‐NMR spectroscopic methods and elemental analysis. Cytotoxic effects of target compounds were determined by 2, 3‐bis‐(2‐methoxy‐4‐nitro‐5‐sulfophenyl)‐2H‐tetrazolium‐5‐carboxanilide assay and compound 1 showed significant cytotoxic activity against both MCF‐7 and MDA‐MB‐231 cells, with half‐maximal inhibitory concentration values of 2.97 μM and 6.57 μM, respectively. Moreover, in this study, the anticholinergic and antidiabetic potentials of these compounds were investigated. To this aim, the effect of the newly synthesized thiosemicarbazone derivatives on the activities of acetylcholinesterase (AChE) and αglycosidase (α‐Gly) was evaluated spectrophotometrically. The title compounds demonstrated high inhibitory activities compared to standard inhibitors with K i values in the range of 122.15–333.61 nM for α‐Gly ( K i value for standard inhibitor = 75.48 nM), 1.93–12.36 nM for AChE ( K i value for standard inhibitor = 17.45 nM). Antiproliferative activity and enzyme inhibition at the molecular level were performed molecular docking studies for thiosemicarbazone derivatives. 1M17, 5FI2, and 4EY6, 4J5T target proteins with protein data bank identification with (1 –11 ) compounds were docked for anticancer and enzyme inhibition, respectively.